Strateji̇k yöneti̇me dayali okul geli̇şi̇m endeksi̇ni̇n oluşturulması : Bi̇r karma yöntem araştırması - Gürkan, Hilal (My University, 2023)
Okul geliştirme sürecinde karşılaşılan en önemli problem, okul gelişiminin çok boyutlu bir yapıya sahip olması nedeniyle bütüncül bir perspektiften ele alınmasının zor oluşudur. Okullar bağlamında 5018 sayılı Kamu Mali Yönetimi ve Kontrol Kanunu kapsamında stratejik planlar yapılmakla birlikte izleme ve değerlendirme aşamasında zorluklar yaşanmaktadır. 11.Kalkınma Planı ve MEB 2023 Eğitim Vizyonu Belgesinde “Okul Gelişim Modeli”ne yer verilmesine rağmen bu modelin stratejik yönetimle entegrasyonuna ilişkin yeterince veri ve bilimsel bir metodolojinin olmadığı görülmektedir. Okul gelişimi için stratejik planlama yeterliliğinin arttırılması gerektiği, stratejik planların ve okul gelişim planlarının etkili birer araç olabilmeleri için iyi bir şekilde tasarlanması ve uygulanmasının sağlanması, stratejik yönetim ve okul geliştirmenin bütünleştirilmesi yönünde literatürde görüşler olmasına rağmen okul geliştirme ile stratejik yönetimin entegrasyonunu sağlayacak bir araştırmaya rastlanmamıştır. Okul gelişiminde rol oynayan boyutlar ve kritik başarı faktörlerinin stratejik yönetimle birlikte ele alındığı ulusal ve uluslararası alan yazında bir okul gelişim endeksi çalışması bulunmamaktadır. Bu çalışma ile okulların gelişimsel ihtiyaçları doğrultusunda stratejik yönetime dayalı bir okul gelişim endeksinin oluşturulması amaçlanmaktadır. Nitel verilerin, çalışmadaki nicel boyutu şekillendirilmesi amaçlandığından araştırmada karma yöntem araştırmalarından keşfedici ardışık desen kullanılmıştır. Okul geliştirme çerçevesini bütüncül bir perspektiften yansıtması açısından okul geliştirme boyutlarını tespit etmek için nitel aşamada doküman analizi kullanılmıştır. Doküman analizinin bibliyometrik göstergeler açısından incelenmesi ile okul gelişiminde ana boyutlar belirlenmiştir. Okul gelişiminde kritik başarı faktörlerinin tespit edilebilmesi için uzman görüşlerinin alınmasına dayanan Delphi tekniği kullanılmıştır. Nitel veri toplama yöntemleri ile elde edilen bilgilerden çıkarımlar yapılarak bir okul gelişim endeksi geliştirilmesi için nicel aşamaya geçilmiştir. Araştırmada okul geliştirme boyutları ve Kritik Başarı Faktörlerinin (KBF) önceliklendirilmesi ve stratejik yönetimle okul geliştirmenin entegrasyonu için Balanced Scorecard (BSC) yaklaşımı temel alınmıştır. Okul geliştirme boyutları ve bu boyutlara ait kritik başarı faktörlerinin arasındaki neden- sonuç ilişkilerinin ortaya çıkarılması için ise DEMATEL yöntemi kullanılmıştır. Okul Gelişim Endeksinde yer alacak performans göstergeleri önce doküman analizi ile tespit edilmiş ardından Lawshe tekniği ile son hali verilmiştir. Çok Kriterli Karar Verme Yöntemlerinden olan SWARA yöntemi ile okul gelişim endeksindeki boyutların, kritik başarı faktörlerinin ve performans göstergelerinin ağırlıkları ve öncelik sıraları belirlenmiştir. Araştırmada amaçlı örnekleme yöntemi kullanılmıştır. Delphi çalışmasında 24 uzman, DEMATEL çalışmasında 12 uzman, kapsam geçerliliği çalışmasında 16 uzman, SWARA aşamasında 6 uzman yer almıştır. Doküman analizi sonucunda okul gelişiminde altı boyut tespit edilmiştir. Bu boyutlar kurumsal kaynak yönetimi, liderlik ve yönetişim, öğretmen performansı, öğrenme-öğretim süreçleri, okul-paydaş ilişkileri, örgütsel iç süreçlerdir. Delphi tekniğine göre okul gelişiminde 21 kritik başarı faktörü tespit edilmiştir. Okul gelişim boyutlarının DEMATEL analizi sonuçlarına göre; Liderlik ve Yönetişim, Örgütsel İç Süreçler ve Okul- Paydaş İlişkileri boyutları sırasıyla en yüksek önem değerlerine sahip kriterlerdir. Okul geliştirme boyutları etki-ilişki yönünden incelendiğinde Liderlik ve Yönetişim boyutunun diğer boyutlara göre merkezi bir rol oynadığı Öğrenme-Öğretim Süreçleri boyutunun ise diğer boyutlardan en çok etkilenen boyut olduğu tespit edilmiştir. Öğretmen performansı boyutu diğer boyutları hem etkileyen hem de diğer boyutlardan etkilenen bir boyuttur. Kritik başarı faktörlerinin DEMATEL analizi sonuçlarına göre; Paydaş Memnuniyeti, Kapsayıcı ve Destekleyici Kurum Kültürü, Paydaşların Motivasyonu faktörleri sırasıyla en yüksek önem değerine sahip kriterlerdir. Kritik başarı faktörleri etki-ilişki yönünden incelendiğinde Liderlik Becerileri ve Öz-Yeterlikleri faktörü diğer faktörler arasında merkezi bir rol oynadığı, Öğrenme Çıktıları kriterinin ise diğer kriterlerden en çok etkilenen kriter olduğu tespit edilmiştir. Etkili Rehberlik ve Mesleki Yöneltme kriteri ise diğer kriterleri hem etkileyen hem de diğer kriterlerden etkilenen bir kriterdir. Okul Gelişim Endeksi için 131 maddelik bir performans göstergesi havuzu oluşturulmuştur. Okul Gelişim Endeksi için Lawshe Tekniği kullanılarak endekste yer alacak 6 boyut, 15 KBF ve 60 performans göstergesi belirlenmiştir. DEMATEL yöntemine göre “Liderlik ve Yönetişim, Örgütsel İç Süreçler, Okul- Paydaş İlişkileri” sırasıyla en yüksek önem değerine sahip ilk üç boyut olurken; SWARA yöntemi ile ağırlıklandırmaya göre “Liderlik ve Yönetişim, Öğretmen Performansı, Öğrenme-Öğretim Süreçleri” en yüksek önem değerine sahip ilk üç boyut olmuştur. SWARA yöntemine göre; okul geliştirme boyutlarının ağırlıklandırılmasında “Liderlik ve Yönetişim” boyutunun en önemli boyut olduğu, kritik başarı faktörlerinin ağırlıklandırılmasında “Öğretmenin Mesleki Bilgisi ve Öz Yeterliği” kriterinin en önemli ana kriter olduğu, performans göstergeleri ağırlıklandırılmasında “Öğretmen Motivasyonunun Artırılmasına Yönelik Etkinlik Sayısı” göstergesinin en önemli performans göstergesi olduğu tespit edilmiştir. Bu araştırmanın okul gelişimi alanında ulusal ve uluslararası bir endeksin olmaması, endeksin çok kriterli karar verme yöntemi ile geliştirilmesi, okul gelişimi alanında Delphi tekniği ile belirlenen okul geliştirme boyutlarına ilişkin kritik başarı faktörlerinin ilk kez literatürde yer alacak olması, kritik başarı faktörleri arasındaki neden sonuç ilişkilerini DEMATEL yöntemi ile açıklaması, okul geliştirme boyutlarıyla Balanced Scorecard (BSC) oluşturulması, endeks kapsam geçerliğinin Lawshe tekniği ile sağlanması, endeks madde ağırlıklarının SWARA yöntemi ile ortaya konulması, ulusal ve uluslararası değerlendirme ölçütlerinden yola çıkılarak okulların stratejik planlarında yer almayan göstergelerin de endekste yer alması, stratejik yönetimle okul gelişiminin bütüncül bir perspektiften ele alınması açısından politika yapıcılara, karar vericilere ve alan yazına katkı sağlayacağı düşünülmektedir. Okul gelişim endeksinin okulları gelişimsel özelliklerine göre sıralaması ve okullar arasında veriye dayalı bir ekosistemin oluşturulmasına katkı sağlayacağı öngörülmektedir.

The most significant challenge encountered in the school improvement process is the difficulty of approaching it from a holistic perspective due to the multidimensional nature. Although strategic plans are prepared for schools within the scope of Law No. 5018, difficulties are experienced in the monitoring and evaluation process. Despite the inclusion of the School Development Model in the 11th development plan and 2023 Education Vision Document, it is observed that there is not enough data and a scientific methodology for the integration of this model with strategic management. Although there are opinions in literature about the need to increase the competence of strategic planning for school development, and to ensure that strategic plans and school development plans are well designed and implemented to be effective tools, there has been no research on integrating school development with strategic management. In national and international literature where dimensions and critical success factors playing a role in school development are discussed, there is no study on a school development index. This study aims to create a school development index based on strategic management in line with the developmental needs of schools. A mixed-method research approach was used in the study to shape the quantitative dimension of qualitative data, employing an exploratory sequential design. In the qualitative phase, document analysis was used to identify school development dimensions to reflect the school development framework from a holistic perspective. By examining document analysis in terms of bibliometric indicators, the main dimensions of school development were determined. To identify critical success factors in school development, the Delphi technique, based on expert opinions, was used. Inferences were drawn from the qualitative data collection methods, and the study transitioned to the quantitative phase to develop a school development index. In the research, the Balanced Scorecard (BSC) approach was used as a basis for prioritizing school development dimensions and critical success factors (CSFs) and for integrating strategic management with school improvement. The Decision-Making Trial and Evaluation Laboratory (DEMATEL) method was used to reveal the cause-and-effect relationships between school development dimensions and CSFs. Performance indicators for inclusion in the School Development Index were first identified through document analysis and then finalized using the Lawshe technique. The School Weighted and Ranked Assessment (SWARA) method was used to determine the weights and priority rankings of dimensions, CSFs, and performance indicators in the School Development Index. The purposeful sampling methods, was used in the research. In the Delphi study, 24 experts participated, 12 experts in the DEMATEL study, 16 experts in the scope validity study, and 6 experts in the SWARA phase. As a result of document analysis, six dimensions of school development were identified. These dimensions are institutional resource management, leadership and governance, teacher performance, teaching and learning processes, school-stakeholder relations, and organizational internal processes. According to the Delphi technique, 21 critical success factors in school development were identified. According to the DEMATEL analysis results of school development dimensions, Leadership and Governance, Organizational Internal Processes, and School-Stakeholder Relations are the criteria with the highest importance values, respectively. When school development dimensions are examined in terms of cause-and-effect relationships, it is determined that the Leadership and Governance dimension plays a central role compared to other dimensions, and the Teaching and Learning Processes dimension is the most affected dimension among others. The Teacher Performance dimension is both a dimension that affects other dimensions and is affected by other dimensions. According to the DEMATEL analysis results of critical success factors, Stakeholder Satisfaction, Inclusive and Supportive Organizational Culture, and Stakeholder Motivation factors are the criteria with the highest importance values, respectively. When critical success factors are examined in terms of cause-and-effect relationships, it is determined that Leadership Skills and Self-Efficacy play a central role among other factors, and the Learning Outcomes criterion is the most affected criterion among others. The Effective Counseling and Career Guidance criterion is a criterion that both affects other criteria and is affected by other criteria. A performance indicator pool consisting of 131 items was created for the School Development Index. Using the Lawshe Technique, 6 dimensions, 15 CSFs, and 60 performance indicators were determined to be included in the index. According to the DEMATEL method, Leadership and Governance, Organizational Internal Processes, School-Stakeholder Relations are the top three dimensions with the highest importance values, while according to the SWARA method, Leadership and Governance, Teacher Performance, Teaching and Learning Processes are the top three dimensions with the highest importance values. According to the SWARA method, the Leadership and Governance dimension is the most important dimension in weighting school development dimensions, the Teacher's Professional Knowledge and Self-Efficacy criterion is the most important main criterion in weighting critical success factors, and the Number of Activities Aimed at Increasing Teacher Motivation indicator is the most important performance indicator in weighting performance indicators. This research is expected to contribute to policymakers, decision-makers, and the literature in terms of approaching school development from a holistic perspective, as there is no national and international index in the field of school development, the index is developed using a multi-criteria decision-making method, it includes critical success factors for school development dimensions determined by the Delphi technique for the first time in literature and explains the cause-and-effect relationships among critical success factors using the DEMATEL method. It also integrates school development dimensions with the Balanced Scorecard (BSC) and ensures the scope validity of the index using the Lawshe technique. Adding that, it reveals the importance of index items using the SWARA method and includes indicators that are not included in school strategic plans based on national and international evaluation criteria. It is anticipated that the school development index will contribute to rank schools according to their developmental characteristics and to create a data-based ecosystem among schools.
Keywords: Kritik Başarı Faktörleri; Okul Gelişim Endeksi Critical Success Factors; Okul gelişim programları; Okul Geliştirme; Okul yönetimi ve örgütü; School Development Index; School Improvement; School improvement programs; School management and organization